A radio production to educate, inform and entertain - Castillo Marín, Johana Marina (Omnia, 2025)
This text describes the importance of radio production based on López (2005), and the use of the sound code according to Casetti and Di Chio (1991, 1997), characterizing the structure and functions of radio sound and arguing the use of various methods that include convergence on the Internet or cyberradio, based on the principles of Cebrián (2009), and currently with the inclusion of Artificial Intelligence (AI). In this qualitative text, it is reviewed, documented and argued theoretically with the technique of observation and the description of the sound reality with the intention of suggesting methods for radio production in radio stations in Venezuela and Zulia state in particular. It is observed that those who like the radio listen to it to enjoy the sounds, entertain themselves and get information. However, everything indicates that the radio must propose in its production and programming content that distributes the proper use of the word, musical selection appropriate to the time blocks, instead of privileging almost exclusively advertising insertion as opposed to educational messages for its users.